Preparation of patients for endoscopic investigations and surgery of the large intestine - B. N. Bashankaev; A. G. Yuldashev; D. F. Yermakov; P. V. Tsarkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate modern approach to preparation of patients for endoscopy and colon and rectal surgery.Original positions. Due to application of polyethylene glycol (PEG) obligatory cleaning of the large intestine became possible without application of flush enemas. PEG is high molecular weight linear polymer retaining water that increases fluid volume in the bowel and stimulates mechanoreceptors. Application of sodium phosphates is an alternative preparation method. Risk of hyperphosphatemia that develops in some groups of patients limits their application. Preparation with excellent cleaning of large intestinal lumen is necessary for conclusive endoscopic investigation. Preparation is required as well before elective laparoscopic and rectal surgery. Authors’ experience of preoperative management of colorectal patients is presented.Conclusion. Application of PEG agents allows to obtain safely high-quality preparation for surgical and endoscopic colorectal interventions with the least number of relative and absolute contraindications.